2017
DOI: 10.3390/toxins9040112
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Pichia membranifaciens Killer Toxins

Abstract: The killer phenomenon is defined as the ability of some yeast to secrete toxins that are lethal to other sensitive yeasts and filamentous fungi. Since the discovery of strains of Saccharomyces cerevisiae capable of secreting killer toxins, much information has been gained regarding killer toxins and this fact has substantially contributed knowledge on fundamental aspects of cell biology and yeast genetics. The killer phenomenon has been studied in Pichia membranifaciens for several years, during which two toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 197 publications
(224 reference statements)
0
43
0
5
Order By: Relevance
“…It has previously been shown that yeast growth can be inhibited by yeast metabolites such as ethanol [40,41], medium chain fatty acids [42], and acetaldehyde [43]. Killer toxins produced during the exponential phase by specific strain can also have an inhibitory impact on some yeast growth [44][45][46]. More recently, it was found that S. cerevisiae could secrete peptides who inhibit non-Saccharomyces yeast growth [47].…”
Section: Yeast Population Kineticsmentioning
confidence: 99%
“…It has previously been shown that yeast growth can be inhibited by yeast metabolites such as ethanol [40,41], medium chain fatty acids [42], and acetaldehyde [43]. Killer toxins produced during the exponential phase by specific strain can also have an inhibitory impact on some yeast growth [44][45][46]. More recently, it was found that S. cerevisiae could secrete peptides who inhibit non-Saccharomyces yeast growth [47].…”
Section: Yeast Population Kineticsmentioning
confidence: 99%
“…Mehlomakulu and coworkers [15] identified two killer toxins, CpKT1 and CpKT2, from the wine-isolated yeast Candida pyralidae. A similar action was described for the killer toxins isolated from Kluyveromyces wickerhamii and Pichia anomala [38], Pichia membranifaciens [26], Torulaspora delbrueckii [25] and Ustilago maydis [39]. Furthermore, an early inoculation with a selected LAB culture has proven to be a useful tool for controlling the proliferation of B. bruxellensis in wine.…”
Section: Introductionmentioning
confidence: 96%
“…The main types of interaction between Saccharomyces spp. and non-Saccharomyces yeasts are: nutritional limitation or competition [23,24] and the release of toxic compounds as killer toxins into the environment [15,25,26]. On the other hand, there are three types of interaction between yeast and LAB.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of the toxin to the yeast cell wall is recognized as the first step of the antifungal action. However, other mechanisms have been discovered, including perturbation of membrane integrity or cell functioning (Belda, Ruiz, Alonso, Marquina, & Santos, 2017;Hatoum, Labrie, & Fliss, 2012;Izgu & Altinbay, 2004). A vast majority of killer toxins have a limited spectrum of activity, display poor stability, and are only active in a narrow range of pH (Santos, San Mauro, Bravo, & Marquina, 2009;Soares & Sato, 2000).…”
Section: Microbial Sourcesmentioning
confidence: 99%